1997
DOI: 10.1093/infdis/175.3.533
|View full text |Cite
|
Sign up to set email alerts
|

The Humoral Immune Response against Human Cytomegalovirus Is Characterized by a Delayed Synthesis of Glycoprotein-Specific Antibodies

Abstract: An individual analysis of IgG antibodies against 12 known antigenic domains of human cytomegalovirus (HCMV)-derived structural phospho- and glycoproteins and nonstructural polypeptides was performed. In HCMV-seropositive healthy persons, the separate determination of antibody titers against the various antigens resulted in an antibody profile that was characteristic for each individual. Profiles were qualitatively stable over a period of >4 years. However, quantitative changes were observed in some persons. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
89
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 51 publications
10
89
1
1
Order By: Relevance
“…gB is the actual fusion mediator, and its fusogenic activity presumably must be triggered via interaction with gH/gL (20,21). In addition, gB is an important immunogen, as gB-specific antibodies can be detected in all naturally infected individuals (22). A major fraction of neutralizing antibodies in sera from HCMVseropositive donors is directed against gB, and the overall neutralizing capacity correlates with the anti-gB antibody titer when tested on fibroblasts (23,24).…”
mentioning
confidence: 99%
“…gB is the actual fusion mediator, and its fusogenic activity presumably must be triggered via interaction with gH/gL (20,21). In addition, gB is an important immunogen, as gB-specific antibodies can be detected in all naturally infected individuals (22). A major fraction of neutralizing antibodies in sera from HCMVseropositive donors is directed against gB, and the overall neutralizing capacity correlates with the anti-gB antibody titer when tested on fibroblasts (23,24).…”
mentioning
confidence: 99%
“…Administration of CMV-HIG has also been shown to be effective in preventing CMV disease in solid-organ transplant (SOT) patients (14,15,20). Many studies have shown that human sera can react with a broad spectrum of CMV proteins from either purified virus or virus-infected cells (1,2,10,13). However, binding to viral components does not necessarily confer protection.…”
mentioning
confidence: 99%
“…An important antibody target is glycoprotein B (gB). Antibodies directed against gB can be detected in all infected individuals (9,10). A major fraction of neutralizing antibodies in human sera seems to be directed against gB, and the overall in vitro neutralizing capacity in sera from HCMV-infected individuals correlates with anti-gB antibody titer (9,11).…”
mentioning
confidence: 99%